Fractional-Order Instrumentation Amplifier Transfer Function for Control Applications - Alimisis, Vassilis; Pappas, Georgios; Sotiriadis, Paul (Symposium on Integrated Circuits and Systems Design (SBCCI), 2020)
This paper explores a new architecture for a fractional-order instrumentation amplifier for control applications. The proposed architecture provides electronic tuning capability and is reconfigurable. It can be configured as either a classic integer-order or a fractional-order instrumentation amplifier, with appropriate tuning of the parameters that define the characteristics of the components involved. The proposed design can be used as a fundamental building block in the implementation of more complex control systems.